Korelasi Glukosa Kapiler Metode Glucose Dehidrogenase-Nicotinamide Adenine Dinucleotide Dengan Glukosa Serum Metode Heksokinase - Fitria, Syarifah Tridani; Yaswir, Rismawati; Efrida, Efrida (Jurnal Kesehatan Andalas, 2021)
Rapid and accurate measurement of capillary glucose level using point-of-care testing (POCT) is needed to maintain the patient’s normoglycemic status in obtaining adequate management. The glucose POCT method should be evaluated to determine analytical performance by comparing with the hexokinase method as a reference method to provide accurate and reliable results. Objectives: To determined the correlation between capillary glucose using glucose dehydrogenase-nicotinamide adenine dinucleotide (GDH-NAD)  and serum glucose hexokinase methods. Methods:  This analytic cross-sectional study on 42 outpatients who underwent fasting blood glucose examination at Dr. M Djamil Padang General Hospital. This study was conducted from February until September 2020. Capillary fasting blood glucose was measured using glucose POCT GDH-NAD method and serum glucose with hexokinase method. The Spearman correlation test was used to analyze data, significant if p<0.05. Results: The subjects were 28 male (66.7%),14 female (33.3%) with mean age and hematocrit level was 56.12±12.97 years and 40.90±2.42%, respectively. The median capillary glucose GDH-NAD method and serum glucose hexokinase method were 100.00 mg/dL each, with a median difference was 3.00 mg/dL. Spearman correlation test showed very strong positive correlation and statistically significant (r=0,961;p=<0,001). Conclusion: Capillary glucose GDH-NAD method had a very strong positive correlation with serum glucose hexokinase method.Keywords:  hexokinase, fasting glucose level, GDH-NAD, glucose POCT